Character moderation readiness: Analysis of elementary school students' viewing readiness - Dewi, Eva Musmala; Sayekti, Octavian Muning; Wibowo, Setiawan Edi (Jurnal Penelitian Ilmu Pendidikan, 2024)
This study investigates the relationship between learning readiness, character moderation, and viewing comprehension skills in elementary school students. Viewing comprehension is increasingly recognized as a crucial language ability for addressing 21st-century challenges and adapting to digital media. The research used a quantitative approach and a descriptive-correlational design with multiple linear regression analyses. It looked at 76 teachers and 76 fifth-grade students from eight elementary schools in Sleman Regency, Yogyakarta. The research instruments included a questionnaire for assessing learning readiness, a questionnaire for character moderation, and a viewing comprehension test based on Minimum Competency Assessment items. Findings show that learning readiness and character moderation don't have a big effect on students' ability to understand what they're watching. An R² value of 0.006 and a significance level of p > 0.05 show that neither factor makes a significant difference. However, this does not rule out the potential for a relationship; thus, it implies the necessity to explore other internal and external variables that may affect viewing comprehension further.